THE IMPACT OF BUDGET PADDING ON INFRASTRUCTURE DEVELOPMENT IN SOUTH EAST GEOPOLITICAL ZONE OF NIGERIA - Uloma Bridget Egwuagu; Nnaemeka Hillary Anikeze; Florence Elochukwu Awah (ESUT JOURNAL OF SOCIAL SCIENCES, 2026)
This study investigated the impact of budget padding on infrastructure development in Nigeria, using the South East geopolitical zone as a case study. The objectives were to examine the extent to which budget padding affects the timely execution and quality of infrastructure projects and to assess the relationship between budget padding practices and the misallocation or diversion of public funds meant for infrastructural development in the region. A descriptive survey research design was adopted to gather data from a cross-section of stakeholders including government officials, legislators, contractors, civil society members, and community leaders across Abia, Anambra, Ebonyi, Enugu, and Imo states. Using a multistage sampling technique, 200 respondents were selected, and data were collected through structured questionnaires. Simple percentages and linear regression analysis were employed to analyze the data and test the hypotheses. The findings revealed a significant relationship between budget padding and the diversion of public funds, as well as its negative impact on the timely execution and quality of infrastructure projects in the South East. The study concluded that budget padding undermines infrastructure delivery by enabling the misallocation of resources and promoting fiscal indiscipline. It recommends enhanced oversight by anti-corruption agencies, civil society, and the National Assembly, alongside strict legal sanctions against individuals found guilty of budget manipulation.